(untitled) (Scientific journal of the Fergana State University, 2024)
This article presents pedagogical analyzes on the correct formation of students’ attitude towards sports, based on their sports orientation, on developing in them a sense of worthy defense of the honor of the country, and not only the physical capabilities of students in Physical education, but also their mental abilities - will, patience - are analyzed, the task of developing their national self-awareness by cultivating dexterity.